Accountability in the Management of Separated State Assets Following the Revision of the State-Owned Enterprises Law: An Analysis of Changes in Danantara's Governance Framework - Iwan Ridwan Waluya; Siti Musriah; Alif Nurfuadi; Ksatria Bintang Fortuna; Riski Saputra Hutabarat (Rechtsvinding, 2026)
The enactment of Law Number 1 of 2025 concerning the Third Amendment to Law Number 19 of 2003 on State-Owned Enterprises established the Daya Anagata Nusantara Investment Management Agency (Danantara), transforming the governance of separated state assets in Indonesia. This study examines the impact of changes in the institutional structure, the expansion of Danantara’s authority, and the supervisory mechanism on the accountability of separated state assets management. Using a normative juridical method with statutory and conceptual approaches, this research analyzes relevant legislation, legal doctrines, and legal literature. The findings indicate that Danantara has shifted the governance model from entity-based management to an integrated investment holding structure, resulting in broader investment authority and a more complex accountability framework. The supervisory mechanism has also evolved from entity-based supervision to group-based supervision, requiring stronger transparency, auditability, traceability, and clearer institutional responsibilities. This study concludes that accountable management of separated state assets depends on a clear allocation of authority, effective supervision, and the consistent implementation of good corporate governance principles.